Temporal structure/function variation in cultured differentiated human nasal epithelium associated with acute single exposure to tobacco smoke or E-cigarette vapor. (23rd February 2017) - Carson, Johnny L.; Zhou, Laura; Brighton, Luisa; Mills, Katherine H.; Zhou, Haibo; Jaspers, Ilona; Hazucha, Milan
Abstract: Objective: Mucociliary clearance sustains a baseline functionality and an "on demand" capability to upregulate clearance upon irritant exposure involving mucus hypersecretion and accelerated ciliary beat frequency (CBF) modulated by nitric oxide (NO). This study characterized these elements as well as cellular and exogenous NO concentrations subsequent to a single exposure to tobacco smoke (TS) or e-cigarette vapor (EV) on cultured human airway epithelium. Materials and methods: Air–liquid interface (ALI) airway epithelial cultures per nonsmoking human subjects were subjected to single TS or EV exposures. Measures of ciliary function and secretion were performed and cellular and exogenous NO concentrations under control and experimental conditions were assessed. Results: Both TS and EV exposures resulted similar patterns of decline in CBF within 1 min of the completion of exposure followed by a gradual return often exceeding baseline within 1 h. Post-exposure examination of exposed cultures suggested morphologic differences in secretory function relative to controls. The relative NO concentrations of TS and EV chamber air were sharply different with EV NO being only slightly elevated relative to cellular NO production. Discussion and conclusions: Epithelial remodeling and mucociliary dysfunction have been clearly associated with TS exposure. However, information contrasting epithelial structure/function following a single acute TS or EV exposure is limited. This study demonstrates a similar pattern of epithelial response to acute TS or EV exposure. Inasmuch as NO may contribute to an inflammatory milieu and generation of toxic metabolites, it is plausible that recurrent exposures over time may be contributory to chronic pathologies.